Complete cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for colorectal peritoneal metastasis in Norway: Prognostic factors and oncologic outcome in a national patient cohort. Issue 2 (12th May 2016) - Frøysnes, Ida S.; Larsen, Stein G.; Spasojevic, Milan; Dueland, Svein; Flatmark, Kjersti
Abstract : Background and Objectives: Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) can offer long‐term survival to patients with resectable peritoneal metastasis (PM) from colorectal cancer (CRC), a condition with otherwise dismal prognosis. This study describes short‐ and long‐term outcome in a national patient cohort and aims to identify prognostic factors. Methods: All patients treated with CRS‐HIPEC for non‐appendiceal PM‐CRC in Norway 2004–2013 were included (n = 119), and outcome and potential prognostic factors were examined using survival‐ and ROC‐curve analysis. Results: Five‐year overall survival (OS) and disease‐free survival (DFS) were 36% and 14%, respectively, with 45 months median follow‐up. The only factor associated with OS in multivariable analysis was peritoneal cancer index (PCI), with HR 1.05 (1.01–1.09) for every increase in PCI‐score ( P  = 0.015). Peritoneal relapse was associated with shorter OS than distant metastasis ( P  = 0.002). ROC‐curves identified PCI > 12 as a marker with 100% specificity for prediction of disease relapse. Severe postoperative complications (Clavien–Dindo ≥ 3) occurred in 15% of patients and there was no 100‐day mortality. Conclusions: Long‐term outcome was in line with published results, morbidity was acceptable and there was no 100‐day mortality. The results reemphasize CRS‐HIPEC as an important treatment option in PM‐CRC, with particularly good results in patients with PCI < 12. J. Surg. Oncol. 2016;114:222–227 . © 2016 Wiley Periodicals, Inc.